Simplified Selvester QRS Score as an Infarct Size Parameter in STEMI Patients Undergoing Pharmacoinvasive or Primary Percutaneous Coronary Intervention - Prasetia, Arif Eka; Hartopo, Anggoro Budi; Taufiq, Nahar; Bagaswoto, Hendry Purnasidha; Setianto, Budi Yuli (The Indonesian Heart Association, 2022)
Background:Cardiovascular disease especially acute myocardial infarct (AMI) is one of the highest cause of mortality worldwide. Majority of AMI comes in the form of ST elevation myocardial infarct (STEMI) that requires timely diagnosis and revascularization management to restore myocardial circulation. The simple method to estimate infarct size is by using simplified Selvester QRS Score to electrocardiogram records, which is a tested method that have good correlation with gold standard, namely cardiac magnetic resonance imaging. Objectives : To investigate difference of infarct size with simplified Selvester QRS score parameter between STEMI patients undergoing pharmacoinvasive compared to primary PCI. Methods: Eighty-two STEMI patients, 41 of pharmacoinvasive and 41 of primary PCI was scored with simplified Selvester QRS score from electrocardiogram recording. Patient data are retroactively taken form Sardjito Cardiovascular Intensive Care (SCIENCE) registry. Scoring of simplified Selvester QRS Score was done by two experienced cardiologist blinded to patient procedure, and results then measured for interobserver agreement with Bland-Altman test. Comparison of QRS Score in pharmacoinvasive and primary PCI group was done with independent sample T test followed with multivariable linear regression test. Results: The means of simplified Selvester QRS score in pharmacoinvasive and primary PCI group is 7.240±3.015 and 8.900±4.188, p=0.043, respectively. Independent sample T test shows significant difference in the simplified Selvester QRS score in pharmacoinvasive and primary PCI group. The multivariable analysis shows that variables other than revascularization method independently influences QRS score are onset, anterior segment ST elevation and ST segment elevation in more > 3 leads in electrocardiogram. Conclusion: There is significant difference in infarct size measured by simplified Selvester QRS score betweem STEMI patient undergoing pharmacoinvasive method compared to primary PCI procedure, which is lower in the pharmacoinvasive group This article has a related Erratum.